A Strike at the Heart - Linas Kontrimas (Parliamentary Studies, 2025)
In his new book, Critique of Political Reason, philosopher Alvydas Jokubaitis draws on the works of Immanuel Kant to answer questions about the nature of politics. The link between the power of decision and politics, as once observed by Hannah Arendt, serves as Jokubaitis’s starting point. In other words, the book carefully analyzes the proximity and amity between aesthetics and politics. With this assumption in mind, the author scrutinizes Kant’s major works and, as it were, fills in the gaps left by the great thinker, where an explanation of the nature of politics might lie. In the newest Jokubaitis’s book, it unfolds in the interpretation of the principles of beauty, taste and aesthetics, which, for the author, are a means of understanding the origins of politics.